Hubungan Persepsi Tubuh, Gangguan Makan, dan Tingkat Kecukupan Gizi dengan Status Gizi Atlet Renang Remaja di Kota Bogor, Indonesia: Correlation Between Body Image, Eating Disorders, and Nutrient Adequacy Level with Nutritional Status of Adolescent Swimmers in Bogor City, Indonesia - Rani Assyifa; Hadi Riyadi (Universitas Airlangga, 2023)
Background: Adolescent swimmers can have negative body images that lead to eating disorders. It can cause nutritional imbalances and changes in body composition and nutritional status. Objectives: This study analyzed the correlation between body image, eating disorders, and nutrient adequacy level with the nutritional status of adolescent swimmers at the OSC and POSSI, Bogor City. Methods: This research design was a Cross-Sectional Study of 21 subjects selected by purposive sampling with several sample criteria. Body perception data were collected using the Contextual Body Image Questionnaire for Athletes (CBIQA), the risk of eating disorders using the Eating Disorders Screen for Athletes (EDSA) questionnaire, and food consumption using the 2x24 hour Food Recall method. Results: The subject's body image correlated with nutritional status (p=0.030 r=0.473) but no correlation with the risk of eating disorders. The risk of eating disorders was not correlated with nutrient adequacy level (except fluid) and nutritional status. However, there was a correlation between nutrient adequacy level with body composition and nutritional status. Conclusions: Most subjects were satisfied with their body shape because they had normal nutritional status. Subjects who have overweight and obese are more worried about their appearance and are at risk of eating disorders. However, their concern for appearance does not change their diet.